Dynamic performance of a real-scale reinforced concrete building test under a corner-column failure scenario. (1st May 2020) - Adam, Jose M.; Buitrago, Manuel; Bertolesi, Elisa; Sagaseta, Juan; Moragues, Juan J.
Highlights: Edge and corner columns are most vulnerable to accidental events. A test was carried out on a purpose-built full-scale RC building structure. A corner-column was suddenly removed. Alternative load paths were identified. Abstract: The topic of robustness and progressive collapse of structures has attracted significant attention within the field of structural engineering recently. This is reflected by the rise in the number of scientific papers published in recent years as well as efforts in reviewing and developing codes for design. Although important numerical and experimental studies have been carried out to date simulating the sudden removal of columns to reproduce the possible consequences of an extreme event, most of these studies focus on subassembly systems and internal columns. Edge and corner columns are most vulnerable to accidental events. This paper gives the results of a test carried out on a purpose-built full-scale reinforced concrete building with a specially designed corner steel column used for the sudden column removal. The test was highly instrumented, involving 38 strain gauges, 38 displacement transducers and 2 accelerometers to monitor the vertical and lateral response. The results were used to analyse the dynamic performance of the structure after the sudden column removal as well as the alternative load paths (ALPs) mobilised during the test (i.e. flexural and Vierendeel action). The test showed a clear dynamic amplification of the strains and displacements (with high peaks); dynamic amplification factors (DAFs) were obtained accordingly. The load initially carried by the removed column was redistributed through the entire building system (not just the neighbouring columns). Tests on full-scale buildings, including the one described here, can be used to compile a database to validate codes and future numerical studies.